2020
DOI: 10.1007/s13555-020-00439-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns, Depression, and Anxiety Among US Patients Diagnosed with Hyperhidrosis: A Retrospective Cohort Study

Abstract: Introduction Hyperhidrosis is associated with social and emotional stress due to limitations on health-related quality of life. This study examined real-world treatment patterns and concomitant depression and/or anxiety in patients with hyperhidrosis. Methods Commercial health plan members in the US with ≥ 2 hyperhidrosis diagnosis codes and/or antiperspirant prescription claims were identified from January 2010 through November 2017. A control cohort (CC) of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Anxiety was found in 12.7% of patients with generalized HH [ 13 ]. In a sample of 44,484 patients with HH, Klein et al determined that patients had a higher odds of depression and anxiety compared with controls at baseline and follow-up [ 14 ]. Using healthcare claims data, they found that a small portion of patients (51.6%) received antiperspirant prescription treatment [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety was found in 12.7% of patients with generalized HH [ 13 ]. In a sample of 44,484 patients with HH, Klein et al determined that patients had a higher odds of depression and anxiety compared with controls at baseline and follow-up [ 14 ]. Using healthcare claims data, they found that a small portion of patients (51.6%) received antiperspirant prescription treatment [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“… Heiskanen et al 2022 [ 13 ] N/A Retrospective study 511 11.6% of patients with primary HH had depression. Klein et al 2020 [ 14 ] N/A Survey study, cross-sectional 44,484 Higher odds of depression and anxiety compared with controls. Majority of patients did not obtain antiperspirant prescription after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The body feedback concept may be extended to vegetative feedback mechanisms: hyperhidrosis is strongly associated with anxiety, and it is conceivable that increased sweating is not only a vegetative manifestation of anxiety but may also have an anxiety-enhancing feedback effect [46][47][48] . Botulinum toxin treatment has been successfully used as a treatment of anxiety disorders associated with hyperhidrosis 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Mental health problems, such as depression and anxiety, in hyperhidrosis patients, have been investigated in previous studies [8][9][10][11][12]. Although patients with hyperhidrosis lack overt psychopathology, their complaints about mental distress appear to be associated with the degree of symptoms and quality of life [13].…”
Section: Introductionmentioning
confidence: 99%